2016
DOI: 10.1136/archdischild-2015-309458
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of sleep quality in children and their resident parents when in hospital

Abstract: Parents identified poor sleep in hospital as a significant additional burden to their child's hospital admission. Importantly, they identified potential improvements to the ward sleep environment. Intervention studies that target modifiable, child-centred alterations to night-time ward culture are recommended, focusing on measurable child and parental outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 31 publications
2
56
1
6
Order By: Relevance
“…10,11 All participants had been previously nominated as experts in providing care to CMC to participate in an expert elicitation process to prioritize quality improvement interventions for CMC. 36 Ten potential participants were contacted by e-mail to request participation; all agreed to participate. Participants were provided with the study abstract and the summary of domains, themes, and representative quotes from parents and health care providers ( Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…10,11 All participants had been previously nominated as experts in providing care to CMC to participate in an expert elicitation process to prioritize quality improvement interventions for CMC. 36 Ten potential participants were contacted by e-mail to request participation; all agreed to participate. Participants were provided with the study abstract and the summary of domains, themes, and representative quotes from parents and health care providers ( Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…It is psychological factors, for example stress, anxiety, worries and difficult thoughts, as well as poor accommodation facilities, noise, bright lights and ward activity that hinder parents’ sleep in hospital (Edéll‐Gustafsson, Angelhoff, Johnsson, Karlsson, & Mörelius, ; Nassery & Landgren, ; Stickland, Clayton, Sankey, & Hill, ; Stremler, Dhukai, Wong, & Parshuram, ). In addition, participation in care may increase the number of disturbances during the night.…”
Section: Introductionmentioning
confidence: 99%
“…Good sleep is necessary for the parents’ and the child's health and well‐being. The disruption of parental sleep during the night for a long period, with frequent awakenings and poor sleep quality, affect and limit the parents' resources to meet the child's needs and maintain parental wellbeing (Angelhoff, Edéll‐Gustafsson, & Mörelius, ; Lee, Chai, & Ismail, ; Meltzer, Davis, & Mindell, ; Meltzer & Mindell, ; Stickland et al, ). To find interventions that could improve parents’ sleep when staying overnight with their child in hospital it is important to get a deeper knowledge of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are an increasing number of studies that also explore the impact of noise in general children's services. For example, Stickland, Clayton, Sankey, and Hill () in the United Kingdom found that parents and their children experienced reduced sleep quality during hospitalisation. This was attributed to noise and light and ward schedules; parents stated that it challenged their emotional regulation and parent–child relationships.…”
Section: Discussionmentioning
confidence: 99%